2008
DOI: 10.1007/978-3-540-69132-7_37
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Cluster? Automatically Detecting Interesting Interactions in Student E-Discussions

Abstract: Abstract. Students in classrooms are starting to use visual argumentation tools for e-discussions -a form of debate in which contributions are written into graphical shapes and linked to one another according to whether they, for instance, support or oppose one another. In order to moderate several simultaneous e-discussions effectively, teachers must be alerted regarding events of interest. We focused on the identification of clusters of contributions representing interaction patterns that are of pedagogical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Interestingly, the results we achieved with this data improved upon most of the results reported on a different data set, with different annotated cluster types (Mikšátko & McLaren, 2008). More specifically, the DOCE algorithm generally performed better in finding snippets of ''creative reasoning" than it did in finding more standard argumentation structures, such as ''chain of opposition" (i.e., a chain of contributions by students in which they go back in forth in argue for and against a given issue) and ''argument + evaluation" (i.e., a student makes an argument which is then evaluated by another student).…”
Section: Results On the Effectiveness Of The Computational Modelsupporting
confidence: 61%
See 4 more Smart Citations
“…Interestingly, the results we achieved with this data improved upon most of the results reported on a different data set, with different annotated cluster types (Mikšátko & McLaren, 2008). More specifically, the DOCE algorithm generally performed better in finding snippets of ''creative reasoning" than it did in finding more standard argumentation structures, such as ''chain of opposition" (i.e., a chain of contributions by students in which they go back in forth in argue for and against a given issue) and ''argument + evaluation" (i.e., a student makes an argument which is then evaluated by another student).…”
Section: Results On the Effectiveness Of The Computational Modelsupporting
confidence: 61%
“…However, in an earlier experiment, reported in (Mikšátko & McLaren, 2008), we compared DOCE to a simple program that returned random clusters and found that DOCE performed significantly better. While the random algorithm is, admittedly, a ''low bar" to exceed, doing significantly better than random demonstrated that DOCE is clearly finding (at least some) clusters of interest.…”
Section: Evidence Of the Effectiveness And Usability Of The Computatimentioning
confidence: 99%
See 3 more Smart Citations